Public Officials and Their Institutional Environment : An Analytical Model for Assessing the Impact of Institutional Change on Public Sector Performance - Manning, Nick; Mukherjee, Ranjana; Gokcekus, Omer (World Bank, Washington, DC, 2014)
To perform well, public officials must be confident enough about the future, to be able to see a relationship between their efforts, and an eventual outcome. Their expectations are shaped by their institutional environment. If the rules are not credible, or are unlikely to be enforced, of if they expect policies to be contradicted, or resources to flow unpredictably, results will be uncertain, so there is little point in working purposefully. The authors present an analytical framework, used to design a series of surveys of public officials' views of their institutional environment, and to analyze the information generated in fifteen countries. They describe how survey results help map public sector's strengths, and weaknesses, and offer an approach to identifying potential payoffs from reforms. The framework emphasizes how heterogeneous incentives, and institutional arrangements are within he public sector. It emphasizes how important it is for policymakers to base decisions on information (not generalizations) that suggests what is most likely to work, and where. In building on the premise that public officials' actions - and hence their organization's performance - depend on the institutional environment in which they find themselves, this framework avoids simplistic anti-government positions, bur doesn't defend poor performance. Some public officials perform poorly, and engage in rent seeking, but some selfless, and determined public officials, work hard under extremely difficult conditions. This framework offers an approach for understanding both bad performance, and good, and for presenting the results to policymakers in a format that leads to more informed choices, about public sector reform. Types of reforms discussed include strengthening the credibility of rules for evaluation, for record management, for training, and for recruitment; ensuring that staff support government policy; preventing political interference, or micro-management; assuring staff that they will be treated fairly; and, making government policies consistent.